EMPATHY THROUGH EXPERIENCE: AN INTERACTIVE PEDAGOGICAL MODEL FOR PREPARING FUTURE TEACHERS TO SUPPORT CHILDREN WITH CHRONIC ILLNESS - Elena Nedeva (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This article presents an innovative experiential learning model developed for prospective teachers as part of a university course on supporting children with chronic illnesses and their families. The model incorporates rhythmic group synchronisation exercises, emotionally resonant storytelling, real-life video testimonies, student-devised theatrical performances, and a guided closed-eye visualisation—one of the most impactful elements. These practices are designed to cultivate empathy, emotional literacy, and inclusive pedagogical competencies. During the course, students metaphorically represent illness through original stories, intentionally avoiding diagnostic labels in order to reduce stigma. These narratives are then transformed into short theatrical performances that enable participants to embody both physically and emotionally in the lived experiences of children with chronic conditions. A mixed-methods evaluation was conducted. A structured observation protocol captured students’ engagement, emotional reactions, initiative, and collaboration during practical sessions. A post-course Likert-scale questionnaire measured their self-perceived development of empathy and preparedness for inclusive teaching. The results demonstrated a strong alignment between observed behaviour and students’ self-assessments, confirming both the emotional impact and the practical relevance of the model. Grounded in the theories of experiential learning (Dewey, Kolb), social constructivism (Vygotsky), narrative pedagogy (Freire), multiple intelligences (Gardner), and socio-emotional learning (CASEL), the model offers a replicable and emotionally engaging approach to preparing future teachers to work in inclusive educational contexts.